Motivasi Prajurit Dalam Pelaksanaan Tugas - Sentot, Sudiyarto (Jurnal Riset Ekonomi dan Bisnis, 2008)
The Soldiers of TNI will be often getting task outside their regular task. From the result of practice in handling task, professionalism degradation and soldiers discipline can be raised by the basic norms deviation. By this factor, it is very needed to learn the element which is influence that motivation knowing the majority factor that is influence the soldier motivation and how the chief can conduct the Duty as well as his perform to build the soldier motivation.The objective of the research is using the couple linear regression. The result of the simultaneous test it show wages, work condition, chief attention, and social welfare have a real effect to soldier motivation in handling the task. As the result, wages, work condition, social welfare haven’t attract the soldier motivation yet, it just influenced by chief attention, it means the soldier will be in fully motivation only by the chief attention for doing conduct the task.Keywords : wages, work condition, chief attention, social welfare, soldier motivation, handling the task